Pelapisan Sosial Masyarakat Melayu-Jawa Pada Masa Kesultanan Palembang Abad 19 - Dewi Setyawati; Yuliarni Yuliarni (Program Studi Pendidikan Sejarah Universitas Riau, 2021)
This article is to find out the social layers of the Palembang people which began to emerge since the existence of the Palembang Sultanate. In addition to the natives, in the 19th century the population of Palembang had several ethnic groups that had a distinctive settlement in Palembang, namely Chinese, Arab, and Malay-Javanese Palembang. However, the social stratification of this society is focused on the Malay-Javanese community (Ilir Palembang area). During this sultanate, the population was divided into two major groups, namely the aristocratic aristocracy and the common people. The purpose of this study is to analyze the relationship between layers of Malay-Javanese society (Ilir area of Palembang) and their role in each area of social stratification of society. This research is qualitative in nature using literature studies and interviews. The results showed that the people of Palembang, especially Malay-Javanese, had social layers, the area of social stratification of the people of Palembang had a role as a production area for the Palembang Sultanate Period, the Malay-Javanese people of Palembang had titles that determined the Goo-gook area, and Palembang community relations, especially Malay-Javanese. with immigrant communities such as ethnic Arabs, Chinese, and Indians they live side by side with high tolerance.